Real exchange rate response to capital inflows: A dynamic analysis for Ghana - Maxwell Opoku-Afari; Oliver Morissey; Tim Lloyd (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2004)
One of the most challenging problems in developing countries such as Ghana is exchange rate management, that is, 'getting the exchange rate right' especially in the context of exchange rate misalignment. The major research and policy question is what constitutes the equilibrium real exchange rate (ERER) and how can it be measured? Acknowledging the importance of fundamentals in determining the equilibrium real exchange rate, the paper concentrates on the effects of capital inflows (by decomposing capital inflows into official inflows, 'permanent' inflows and 'non-permanent' inflows). Vector Autoregressive (VAR) techniques are used to model the long-run equilibrium real exchange rate in Ghana, and based on a multivariate orthogonal decomposition technique, the equilibrium steady state path is identified which is used in estimating misalignments. As predicted by the Dutch Disease theory, results indicate that capital inflows tend to appreciate the real exchange rate in the long-run. Capital inflows is the only variable generating real appreciation in the long-run; technology change, trade (exports) and terms of trade all tend to depreciate the real exchange rate. The only variable that has a significant (depreciating) effect on the real exchange rate in the short-run is trade, implying that changes in exports are the major driver of exchange rate misalignment. It is also shown that the real exchange rate is slow to adjust back to equilibrium, implying policy ineffectiveness or inflexibility.
Keywords: F31; F35; O11; O55; 330; Capital Inflows; Aid; Real Exchange Rate; Ghana